Numerical investigation of heat transfer enhancement by using louvered-winglet vortex generators mounted in a solar air heater channel-type - Duarte, Rafael M. D.; Salviano, Leandro O. [UNESP]; Ferreira, Wallace G.; Dezan, Daniel J. (Springer Nature, 2023)
The solar air heater (SAH) equipped with special modified surface geometries is one of the existing technologies capable of converting the solar energy into thermal energy with low associated pressure drop, and it has been used as heat source in a wide range of thermal applications which demand lower operating temperatures (about 30 to 80 °C). In the present research, the use of louvered-winglet longitudinal vortex generators as a passive heat transfer enhancement technique is proposed to numerically investigate the effect of the opened louvers have on the SAH thermo-hydraulic performance for: (i) Reynolds numbers of 5000 and 20,000, (ii) two different types of longitudinal vortex generators (delta winglets and rectangular winglets), (iii) aspect ratios of 2 and 6, (iv) angles of attack of 30° and 45°, (v) ratio between louver area and LVG area of 0.25 and 0.44, (vi) louver flap angles of 10°, 40°, and 60° and, (vii) louver opening direction–pointing to the adiabatic plate or to the absorber plate, both downstream of the main flow. The numerical simulations showed that louvered winglets mounted in common-flow-down configurations are thermo-hydraulically more efficient than the respective non-louvered winglets. Rectangular winglets and higher values of ratio between louver area and winglet area, louver flap angle, and aspect ratio promoted a better thermos-hydraulic performance of the channel. The effect of louver on performance of the SAH channel is more pronounced on rectangular winglet than delta winglet. Moreover, the winglets with louvers toward the adiabatic plate introduce less pressure loss to the SAH than the ones with louvers toward the absorber plate. Maximum thermal enhancement factor of 3.418 was achieved for Re = 20,000. With respect to flow patterns and heat transfer characteristics observed on louvered winglets, a new vortex structure generated by the louver openings is identified, in which is responsible to enhance the hot and cold flow mixing. Finally, the louver presents similar effect on thermo-hydraulic performance of the channel, independently of the Reynolds number.
Keywords: Longitudinal vortex generator; Louver fins; Numerical model; Solar air heater; Thermo-hydraulic performance